Volatile Constituents of the Leaf Essential Oil of Crinum asiaticum and their Antimicrobial and Cytotoxic Activities. Issue 4 (4th July 2019) - Tan, Wen-Nee; Shahbudin, Farah Nabilah; Mohamed Kamal, Nik Nur Syazni Nik; Tong, Woei-Yenn; Leong, Chean-Ring; Lim, Jun-Wei
Abstract: Crinum asiaticum, locally known as " bunga tembaga suasa " in Malaysia has been used since ancient ages in folk medicine. The present study was aimed to examine the volatile constituents of the leaf essential oil of C. asiaticum and their antimicrobial and cytotoxic activities. The chemical constituents obtained by hydrodistillation were analyzed using GC and GC/MS. Seventeen constituents were identified in the leaf essential oil, representing 93.14 % of the sample. The major constituents found in the leaf essential oil were 1-hexadecanol (27.69 %), oleic acid (23.32 %) and methyl octadecanoate (12.45 %). In the in vitro MTT assay, the leaf essential oil induced cytotoxic effects of 20-25 % towards MCF-7 cells within 24-72 h of incubation period at 20-70 mg/ml. Moreover, the leaf essential oil also showed antimicrobial activity against Shigella boydii, Candida albicans and Rhizopus sp . with MIC values of 1.25, 0.078 and 0.078 mg/ml, respectively.